2017
DOI: 10.1186/s12887-017-0871-3
|View full text |Cite
|
Sign up to set email alerts
|

Physician practice in food allergy prevention in the Middle East and North Africa

Abstract: BackgroundA number of scientific organisations have developed guidelines for the primary prevention of allergic disease through nutritional interventions. However, even if the best evidence-based guidelines are available, these guidelines do not necessarily lead to adherence and improved health outcomes.MethodTo determine how closely the practice of physicians in select Middle Eastern and North African countries compares with the current recommendations on the primary prevention of allergy a survey study was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
1
6
0
2
Order By: Relevance
“…Although we found that the most common source of maternal information was health care professionals, we noted that only 18.6% and 13.2% among both the at-risk food allergy group and the one without risk, respectively, received proper information about the timing of the introduction of allergenic foods. These findings were consistent with those reported among some Middle Eastern countries, including Saudi Arabia, which showed that their physicians do not adhere to the clinical practice guidelines of infant food counseling [ 15 ]. It would be beneficial if primary health care centers provide a generalized checklist of counseling topics to be filled during each well-baby visit.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although we found that the most common source of maternal information was health care professionals, we noted that only 18.6% and 13.2% among both the at-risk food allergy group and the one without risk, respectively, received proper information about the timing of the introduction of allergenic foods. These findings were consistent with those reported among some Middle Eastern countries, including Saudi Arabia, which showed that their physicians do not adhere to the clinical practice guidelines of infant food counseling [ 15 ]. It would be beneficial if primary health care centers provide a generalized checklist of counseling topics to be filled during each well-baby visit.…”
Section: Discussionsupporting
confidence: 90%
“…Also, a previous study by Vandenplas et al. found that a considerable number of physicians from selected Middle Eastern and North African countries do not follow current recommendations on the prevention of food allergy through the early introduction of allergenic foods [ 15 ]. To our knowledge and on the basis of literature review, no similar studies have been carried out to shed light on this issue in the region.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that there was low level of knowledge about CMA among the studied group. In 2017, Vandenplas et al (5) reported similar finding when they evaluated the adherence of 1,481 physicians (66.1% pediatricians and 7,1% pediatric gastroenterologists) from Middle Eastern and North African countries regarding primary prevention of food allergy, and 60% recommended delayed introduction of potentially allergenic foods.…”
Section: Discussionmentioning
confidence: 83%
“…A Brazilian study reported that 41.9% of pediatricians and nutritionists recommended delayed introduction of allergenic foods in allergic infants [23]. In 2017, Vandenplas et al [32] reported a similar finding when they evaluated the adherence of 1,481 physicians (66.1% pediatricians and 7,1% pediatric gastroenterologists) from Middle Eastern and North African countries regarding primary prevention of food allergy, and 60% recommended delayed introduction of potentially allergenic foods. In our study, 51.6% of those surveyed did not adhere to the guidelines regarding the introduction of complementary feeding to children already diagnosed with CMA, and most of them did not know if this practice complied with the guidelines.…”
Section: Discussionmentioning
confidence: 89%
“…However, adherence to guidelines is usually poor, despite all efforts made in their implementation [28]. There are several international food allergy guidelines [7][8][9][10][12][13][14][15][16], as well as Brazilian consensuses [25,29,30], but there are as yet few studies that evaluate the adherence of pediatricians to these recommendations [23,31,32]. As our questionnaire evaluated adherence to international guidelines, it may be used elsewhere without restriction.…”
Section: Discussionmentioning
confidence: 99%